Effectiveness of psychosocial interventions for the prevention and treatment of foot ulcers in people with diabetes: a systematic review. Issue 8 (23rd June 2020) - Norman, G.; Westby, M. J.; Vedhara, K.; Game, F.; Cullum, N. A.
Abstract: Aim: To identify and synthesize the evidence for the effectiveness of psychosocial interventions to promote the healing, and/or reduce the occurrence of, foot ulceration in people with diabetes. Methods: In March 2019 we searched CENTRAL, Medline, Embase and PsycInfo for randomized controlled trials of interventions with psychosocial components for people with diabetes. The primary outcomes of this review were foot ulceration and healing. We assessed studies using the Cochrane risk‐of‐bias tool, the TIDieR checklist and GRADE. We conducted narrative synthesis and random‐effects meta‐analysis. Results: We included 31 randomized controlled trials (4511 participants), of which most (24 randomized controlled trials, 4093 participants) were prevention studies. Most interventions were educational with a modest psychosocial component. Ulceration and healing were not reported in most studies; secondary outcomes varied. Evidence was of low or very low quality because of high risks of bias and imprecision, and few studies reported adherence or fidelity. In groups where participants had prior ulceration, educational interventions had no clear effect on new ulceration (low‐quality evidence). Two treatment studies, assessing continuous pharmacist support and an intervention to promote understanding of well‐being, reported healing but their evidence was also of very low quality. Conclusion: Most psychosocial intervention randomized controlled trials assessing foot ulcer outcomes in people with diabetes were prevention studies, and most interventions were primarily educational. Ulcer healing and development were not well reported. There is a need for better understanding of psychological and behavioural influences on ulcer incidence, healing and recurrence in people with diabetes. Randomized controlled trials of theoretically informed interventions, which assess clinical outcomes, are urgently required. (PROSPERO registration: CRD42016052960). What's new?: Foot ulcers in people with diabetes are associated with high levels of morbidity, and have been linked to multiple psychosocial factors. Despite identifying 31 randomized controlled trials (4511 participants) we found only low‐quality evidence for a range of psychosocial interventions; there were no clear effects on ulceration or ulcer healing. Reporting of key outcomes and intervention characteristics was limited. Our review highlights the lack of reliable evidence to inform clinical practice and the need for adequately powered, rigorously designed studies to assess theoretically informed psychosocial interventions for clinical outcomes such as ulcer incidence, recurrence, healing and ulcer‐free time.